2012
DOI: 10.7585/kjps.2012.16.2.098
|View full text |Cite
|
Sign up to set email alerts
|

The residue property of fungicide boscalid and fluidioxonil at the same time harvest leafy-vegetables

Abstract: In order to use in the classification of minor crop for the mutual application of safe use guideline, it was investigated the residue property of fungicide boscalid and fludioxonil at the same time harvest leafy-vegetables, such as spinach, ulgaribaechu, vitaminchae and cheongkyungchae. After pesticides were applied 2 times with 1 week interval in that day of harvest, 2 days, 5 days and 7 days before harvest, vegetables were harvested, and the residue of pesticides was investigated. Base on the residue in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
2
2
0
1
Order By: Relevance
“…The half-life was approximately 17 days, as determined using a first-order kinetic model; it was longer than the biological half-life. This result showed that the concentration of residual pesticides decreases as Chinese cabbage grows; a similar result was also reported through a linear regression curve for the dissipation of pesticide residues sprayed on cabbage [ 36 ]. Excluding the dilution effect, the residues were 0.265 and 0.131 mg kg −1 at 0 and 14 days after the last spraying, respectively, and the equation for the dissipation curve was y = 0.2257 × e −0.0515x (r 2 = 0.6206) ( Figure 4 ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The half-life was approximately 17 days, as determined using a first-order kinetic model; it was longer than the biological half-life. This result showed that the concentration of residual pesticides decreases as Chinese cabbage grows; a similar result was also reported through a linear regression curve for the dissipation of pesticide residues sprayed on cabbage [ 36 ]. Excluding the dilution effect, the residues were 0.265 and 0.131 mg kg −1 at 0 and 14 days after the last spraying, respectively, and the equation for the dissipation curve was y = 0.2257 × e −0.0515x (r 2 = 0.6206) ( Figure 4 ).…”
Section: Resultssupporting
confidence: 82%
“…This can be attributed to the larger exposed surface area-to-mass ratio in shallots than in Chinese cabbage and the dilution effect, as Chinese cabbage is heavier than shallots [ 35 ]. Bae et al [ 36 ] sprayed boscalid and fludioxonil on leafy vegetables, such as spinach, Chinese cabbage, tatsoi, and Chinese vegetables and found that the amount of pesticide residue in spinach was 2.5–3.0 times higher than that in the other leafy vegetables. This result was attributed to the growth velocity, leaf surface, life-form, and specific surface area characteristics of the test crops.…”
Section: Resultsmentioning
confidence: 99%
“…Although cabbage and Brussels sprout have a similar wrapped-over form, the half-lives are different because of the hypertrophy of cabbage. The half-life of fludioxonil in Brussels sprout (9.1 days) was similar to that noted in mandarin (8.7 days) 29 and longer than that noted in Chinese cabbage (4.0 days) 28 . Mandarins have a bumpy surface, and pesticides are, therefore, likely to adsorb to the surface.…”
Section: Resultssupporting
confidence: 76%
“…Some previous studies have assessed the dissipation behavior of indoxacarb in cabbage 25 , tomato 26 , and green chili fruit 27 . Bae et al 28 and Hwang et al 29 conducted studies on the half-life of fludioxonil in mandarin and Chinese cabbage, respectively. However, to the best of our knowledge, no studies have assessed the dissipation behavior of the aforementioned eight pesticide residues in Brussels sprout yet.…”
Section: Introductionmentioning
confidence: 99%
“…(Table 5). 엇 갈이배추 재배 기간 중 시험농약의 생물학적 반감기에 대한 여러 연구자들의 결과는 chlorothalonil 7.45일, indoxacarb 4.2일, lufenuron 5.85일, methalaxyl 1.75일, methomyl 2.42 일, boscalid 7.4일, fludioxonil 4.0일, bifenthrin 2.5일, lamda-cyhalothrin 3.6일, deltamethrin 2.9일로 각각 조사되 었다 (Ko et al, 2008;Bae et al, 2012;Kim et al, 2007). 이러한 결과는 bistrifluron과 fluopicolide의 생물학적 반감 기와 큰 차이를 보이지 않는 것으로 판단되며, 엇갈이배추 중 농약의 생물학적 반감기는 시험농약의 이화학적 특성 및 작물의 비대생장에 의한 증체율에 따른 희석효과가 농 약의 생물학적 반감기를 결정하는 중요한 요인으로 판단되 었다.…”
Section: 각의 농약과 해당 작물에 대한 Mrl과 농산물 재배 시 사용 하는 농약의 잔류 소실양상 및 생물학적 반감기에unclassified